Glimpses into cooking practices—observations on past and present Sudanese griddle baking - Ulrike Nowotnick (Afriques)
Flat griddle plates used for baking flatbreads are found in various regions across northern Africa. Morphologically similar cooking implements have been recovered in early Iron Age settlements of Sudan and Ethiopia. The paper discusses the archaeological evidence from Sudan which attests to a widespread use of ceramic griddles for the past 2500 years, about a thousand years earlier than previously thought. As the baking of bread occupies a special place in African food preparation techniques, the early use of griddles in Sudan has sparked debate on the emergence of this cooking technique in Africa: whether it was an indigenous innovation or an adoption from abroad.An ethno-archaeological case study on current griddle cooking in Sudan examines the operational sequence, the tools and social circumstances involved in the baking of flatbreads on griddle plates, locally called doka. Revealing close parallels to the finds from the early Iron Age, traditional griddle cooking provides a chance to better contextualise the use of similar kitchen utensils in the past.